Effect of arbuscular mycorrhiza and rhizobium on physiology and yield of peanut under drought conditions - Chorkaew Aninbon; Pattrarat Teamkao; Kiattisak Buram; Tipawan Kaewnoo; Ruttanachira Ruttanaprasert; Anon Janket; Yi Yi Mon; Phissanu Kaewtaphan (My University, 2024)
Drought is the one primary issue limiting peanut growth and productivity. The study aimed to investigate the effects of arbuscular mycorrhizal fungi (AMF), rhizobium (Rhi), and their combinations on phenolic content, proline content, growth, and yield of peanut under different soil water regimes. The pot experiments were carried out for two growing seasons under greenhouse conditions and designed based on a 2×3 factorial in randomized complete block design (RCBD) with four replications. Factor A comprised two soil water regimes: field capacity (FC) and 1/3 available soil water (1/3 AW), whereas factor B included three different types of microorganisms: (i) uninoculated control, (ii) arbuscular mycorrhiza (AMF), and (iii) a combination of AMF and rhizobium (Rhi) inoculations. Data were collected for growth, proline content, phenolic content, yield, and yield components. Drought stress significantly reduced in relative water content, leaf area, biomass, yield, and yield components of peanut, whereas leaf phenolic content was increased under drought stress. Higher pod dry weight was achieved under FC conditions (28.87 g plant
Keywords: Arbuscular mycorrhiza; Arbuscular mycorrhizal fungi; Legume Nitrogen Fixing Symbiosis